Une histoire du piano au Conservatoire de musique de Paris 1795-1850 - La Grandville, Frédéric de; Badura-Skoda, Paul 1927-2019 (Paris L'Harmattan, 2014)
How did the piano become part of our society? How was its playing, teaching and distribution understood when it appeared at the end of the 18th century? The world-famous Paris Conservatoire appears to be the ideal place to explore these questions. How did it evolve from a military music school to a notion of “music for society”? What about female students? How do you recruit teachers? What is the value of Conservatoire competitive examinations on the “job market”? (Translated with DeepL.com)
Keywords: Conservatoire de Paris (France); 18th Century (1701-1800); 19th Century (1801-1900); Music history; Piano; Paris (France)